1981
DOI: 10.1079/bjn19810078
|View full text |Cite
|
Sign up to set email alerts
|

Fibre and bowel transit times

Abstract: 1. Bowel transit time has been investigated in vegetarians and non-vegetarians and related to dietary fibre intake 2. Vegetarians who have less diverticular disease than non-vegetarians have more rapid transit times. 3. Subjects with total dietary fibre intake of more than 30 g/d all had transit times of less than 75 h whereas 4. Individuals with diverticular disease were found to have faster transit times than those without the disease. 5. The colon may respond to a fibre-depleted diet either by becoming hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 6 publications
1
18
0
3
Order By: Relevance
“…The lower bound is approximately 24 h, which is about as fast as the microbe can cycle through the intestinal track without colonization. [49][50][51] The upper bound is approximately 70 years, which is the longest period of colonization without cycling and corresponds favorably with the maximum life span of the host. 52 The optimum value for the cycle time, as determined by the optimum value for demand ͓from Figs.…”
Section: Life Cycle Provides the Context For Gene Controlmentioning
confidence: 99%
“…The lower bound is approximately 24 h, which is about as fast as the microbe can cycle through the intestinal track without colonization. [49][50][51] The upper bound is approximately 70 years, which is the longest period of colonization without cycling and corresponds favorably with the maximum life span of the host. 52 The optimum value for the cycle time, as determined by the optimum value for demand ͓from Figs.…”
Section: Life Cycle Provides the Context For Gene Controlmentioning
confidence: 99%
“…Stool frequency is impacted by an individual's health (see physical form section) as well as their fibre intake which is associated with more rapid transit times (Gear et al, 1981). Fibre intake has been positively correlated with stool frequency (r = 0.8, p < 0.001 wet weight; r = 0.5, p = 0.008 dry weight) (Southgate et al, 1976).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…53 Gear et al 54 also concluded that a high intake of dietary fibre is associated with more rapid transit times.…”
Section: Fibre and Constipationmentioning
confidence: 99%